Misa-Castro & Associates Law Office a production systems study - Olegario, Audrey; Pardinas, Michael; Pulido, Ma. Rowena (Diliman, Quezon City College of Engineering, 1992)
This paper is a service system study conducted in Misa-Castro and Associates Law Office located in Makati. The law firm is analyzed using different industrial engineering tools, especially principles of production planning and control systems. Misa-Castro and Associates Law Office is a very young firm, being established only in 1991. Its partners, Atty. Misa and Atty. Castro, worked formerly in Asia's largest law office -- the Sycip, Salazar, Hernandez and Gatmaitan Law Office. At present, the firm is composed of the two partners, six associates, and several non-legal personnel. The group visited the law office several times for the past two months. After reviewing the daily service reports of the two partners and four associates, three problem areas were identified. These are problems concerning the personnel (both legal and non-legal staff), the accounting system and the evaluation system. About the legal staff, the utilization rate of the lawyers (partners and associates) differs significantly and the reasons for such were traced back to the organizational set-up and the assignment of cases. With the non-legal staff, work distribution and job description are not clearly defined, resulting to overlapping of responsibilities. The problem with the accounting system is that the manner of preparing the bills to charge the firm's client and the recording of cash advances is most efficient. As to the evaluation system, the present system needs further improvement to have a better basis of reviewing each lawyer's performance. Several alternatives were generated per problem area. These alternatives were evaluated based on a set of criteria decided upon by the group. After determining the final set of alternatives to recommend to the law office, these alternatives were classified undertow categories -- short term and long term alternatives.
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Misa-Castro and Associates; Law firms; Production engineering